Educational Programs for Transferring Success in New York State. Programs That Work. Part C. Title IV 1976-77 - New York State Education Dept., Albany; New York State Education Dept., Albany ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This booklet presents brief descriptions of 13 demonstration projects developed by school districts and other educational organizations in New York, using funds granted under Title IV-C of the Elementary Secondary Education Act. Each of the program descriptions includes the title of the demonstration project, a brief discussion of the project and its objectives, a list of the services available to other interested school districts, and the name and address of a person to contact for further information about the project. (JG)
Sponsoring Agency: Bureau of Elementary and Secondary Education (DHEW/OE), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Development; Demonstration Programs; Educational Innovation; Elementary Secondary Education; Federal Programs; Mathematics Instruction; Program Descriptions; Reading Instruction; Special Education; Elementary Secondary Education Act Title IV C; New York; Reports, Descriptive